EXPLORING APPROACHES FOR INVESTIGATING PHYTOCHEMISTRY: METHODS AND TECHNIQUES - Rohit Saxena (PT. Radja Intercontinental Publishing, 2023)
The extraction, isolation, and analysis of bioactive compounds from plants are fundamental in the study of medicinal plants. This review explores various techniques and methods used for the extraction, isolation, and analysis of bioactive compounds from plant materials. Traditional methods such as maceration, percolation, and Soxhlet extraction are commonly used, but novel techniques have emerged to enhance efficiency and selectivity. Microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), pressurized liquid extraction (PLE), supercritical fluid extraction (SFE), and enzyme-assisted extraction are modern approaches that offer improved yields and efficiency. After extraction, bioactive compounds need to be characterized and analyzed. Chromatographic techniques, such as high-performance liquid chromatography (HPLC) and gas chromatography (GC), are commonly employed for separation and quantification. Spectroscopic techniques, including nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS), provide valuable structural information. The continuous development of extraction and analytical techniques contributes to the discovery and utilization of bioactive compounds from plants in various applications. Future research can explore metabolomics, high-throughput screening, chemoinformatics, network pharmacology, multivariate data analysis, and computational modeling to enhance phytochemical investigations. The proposed methods and techniques complement traditional approaches, expanding our understanding of plant chemistry and its potential applications.